Ojek Online dan Eksistensi Budaya Baru - Ahmad Dzikri Aljasiri; Fiki Febriananda; Muhammad Furqon (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
Online motorcycle taxis are a type of job that is in great demand by people today. This is not without reason, with advances in science and technology that are increasingly sophisticated, of course, the types of jobs available are more numerous and varied, keeping pace with the times. In the online motorcycle taxi profession, solidarity is something that is really needed by a community or social group. Basically all societies, as in social groups, need what is called social solidarity, so that the community can continue to exist and survive as a place for coexistence and harmony among group members. This study aims to find out what forms of solidarity between online motorcycle taxi drivers themselves and the social reality regarding work as online motorcycle taxi drivers. In this Researcher's research, the approach that the Researchers are using is an ethnographic approach, because according to the Researchers this approach is an approach that is appropriate to the research subject to be studied. Ethnography focuses on groups that have the same culture and the same work, these groups are like this online motorcycle taxi community.